Assessing hydrological sampling approaches in the Cape Verde frontal zone in November 2017 - Hernández García, Inés; Coca, Josep; Ramos, Antonio; Rodríguez-Santana, Ángel; Machín, Francisco (Scientia Marina, 2024)
The Cape Verde Frontal Zone in the eastern North Atlantic Subtropical Gyre is a complex region where the warm-er North Atlantic Central Water interacts with the colder South Atlantic Central Water, forming the Cape Verde Front (CVF) with a sharp thermohaline gradient. The CVF exhibits high variability due to lateral intrusions, upwelling system filaments, and mesoscale and submesoscale eddy fields. In November 2017, the FLUXES project surveyed the CVZ extensively using shipborne conductivity, temperature, and depth (CTD) measurements, a SeaSoar and two deep gliders equipped with bio-chemical and dynamical instruments. The primary objective of this paper is to intercompare the spatial scales recovered by the different sampling methods in the CVF, incorporating Copernicus numerical model outputs. Wavelet analysis is used for a quantitative assessment of scales resolved by different sampling methods. The results highlight shipborne CTD depth, down to 1500 m, SeaSoar speed, with a 14 h sampling time, and specific capabilities of both the gliders and the SeaSoar in capturing small scales of between 1 and 5 km. The gliders slightly outperformed the SeaSoar in spatial resolution, emphasizing their effectiveness in revealing smaller features in this dynamic zone. El Frente de Cabo Verde (CVF), en el Atlántico Norte oriental, es una región compleja donde el Agua Central del Atlántico Norte, más cálida, interactúa con el Agua Central del Atlántico Sur, más fría, formando un marcado gradiente termohalino. El CVF muestra gran variabilidad debido a intrusiones laterales, filamentos del sistema de afloramiento y remo-linos a mesoescala y submesoescala. En noviembre de 2017, el proyecto FLUXES realizó un extenso muestreo en el CVF mediante mediciones de Conductividad, Temperatura y Profundidad (CTD) desde un barco, un SeaSoar y dos gliders profun-dos equipados con instrumentos bioquímicos y dinámicos. Este artículo tiene como objetivo comparar las escalas espaciales detectadas por los diferentes métodos de muestreo en el ...